Micromechanical finite element analysis of strain partitioning in multiphase medium manganese TWIP+TRIP steel. (15th April 2016) - Latypov, Marat I.; Shin, Sunmi; De Cooman, Bruno C.; Kim, Hyoung Seop
Abstract: In the present contribution, a phenomenological constitutive model of medium manganese steels, in which both twinning-induced (TWIP) and transformation-induced (TRIP) plasticity enhancing mechanisms are activated, is implemented in the finite element framework. The implementation is utilized for the analysis of the full-field strain partitioning in dual-phase microstructure maps obtained from electron backscattering diffraction. The results of the finite element analysis suggest that the strain localization in the studied steel has an alternating character. Specifically, in the low strain region, most of the externally imposed deformation is accommodated by the initially softer austenite. The higher strain hardening rate of austenite due to deformation twinning (TWIP effect) and the mechanically-induced transformation to martensite (TRIP effect) results in a shift of the strain localization to ferrite. This alternating strain localization is a key feature that distinguishes the medium manganese TWIP+TRIP steel. It is shown that this alternating strain localization contributes to the superior mechanical behavior of medium manganese TWIP+TRIP steel reported in the literature. Graphical abstract: